2016
DOI: 10.1111/1742-6723.12657
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics and survival outcomes of out‐of‐hospital cardiac arrest in children and adolescents between 1997 and 2014 in Perth, Western Australia

Abstract: The incidence of paediatric OHCA decreased over time, but survival remained poor. Strategies to strengthen the chain of survival for paediatric OHCA need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Incidence of pediatric OHCA declined from 1997 to 2014 in Perth, Western Australia, particularly among children <1 year of age. 40…”
Section: Secular Trendsmentioning
confidence: 99%
“…Incidence of pediatric OHCA declined from 1997 to 2014 in Perth, Western Australia, particularly among children <1 year of age. 40…”
Section: Secular Trendsmentioning
confidence: 99%
“…However, more contemporary data now raise the possibility of a potential increase in recent years [4,6,36]. Similarly, the incidence of OOHCA <18 years of age has been reported to have decreased from 14.1 (1997-2000) to 8.7 (2011-2014) per 100,000 in Perth, Western Australia [11]. Sudden cardiac death rates have also been observed to have declined elsewhere, including in Sweden, Netherlands, and Japan [37][38][39].…”
Section: Trends In Incidence Rhythm and Survivalmentioning
confidence: 99%
“…Other reports in Australia have estimated an incidence of all SCD ranging from 34.6 to 89.1 per 100,000 [5][6][7][8][9]. Sudden cardiac death figures in younger age groups vary from 1.1 to 8.7 per 100,000 [10][11][12], with corresponding estimates in adults over 18 years of age ranging from 102.0 to 147.8 per 100,000 [13,14]. A few studies [15][16][17] have suggested that the incidence of EMS-treated OOHCA is not dissimilar in New Zealand to Australia [15], and the AusROC Epistry demonstrated a similar incidence of all EMS-attended OOHCAs of 105.5 per 100,000 [3].…”
Section: Australia and New Zealandmentioning
confidence: 99%
“…Survival among infants has been documented between 1.4% and 1.7% . In contrast, overall survival in children of all age groups is generally slightly higher, although varying widely (2.0–12.1%) with median of 8% . In comparison, in‐hospital arrests have a better outcome with 48.5–62% achieving return of spontaneous circulation (ROSC) and 15.4–48.7% surviving to discharge …”
Section: Introductionmentioning
confidence: 99%
“…4,5 In contrast, overall survival in children of all age groups is generally slightly higher, although varying widely (2.0-12.1%) with median of 8%. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In comparison, in-hospital arrests have a better outcome with 48.5-62% achieving return of spontaneous circulation (ROSC) and 15.4-48.7% surviving to discharge. 5,[21][22][23][24][25][26] There are few data on survival in the subgroup of the OHCA paediatric population that was still receiving cardiac compressions on arrival at hospital.…”
Section: Introductionmentioning
confidence: 99%